Efektivitas Media FlipHoot dalam Meningkatkan Hasil Belajar Pendidikan Pancasila di Sekolah Dasar - Khoirunnisa, Rizkiyanti; Rondli, Wawan Shokib; Fakhriyah, Fina (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to evaluate the effectiveness of FlipHoot media in enhancing learning outcomes in Pancasila Education among ten fifth-grade students at SD 3 Jojo. By utilizing a quantitative approach, this research seeks to measure the extent to which FlipHoot can improve students' comprehension and mastery of the subject matter.Method – A quantitative research design was employed, with a test instrument serving as the primary tool for data collection. The study utilized a pretest-posttest comparison to assess learning improvement, complemented by the N-Gain test to quantify the effectiveness of the intervention. Data analysis was conducted to determine whether the use of FlipHoot contributed significantly to students' academic performance.Findings – The results demonstrate a substantial improvement in student learning outcomes. The average pretest score of 44% increased to 86.5% in the posttest, reflecting a 42.5% enhancement in student comprehension. Furthermore, the N-Gain score of 0.75 indicates a high level of effectiveness, confirming that FlipHoot media successfully aids in strengthening students' understanding and mastery of Pancasila Education concepts. This suggests that the integration of digital learning tools can facilitate better knowledge retention and engagement among students. Research Implications – The findings of this study highlight the potential of FlipHoot media as an effective educational tool that fosters interactive and engaging learning experiences. By simplifying complex concepts and making learning more dynamic, FlipHoot not only benefits students by improving their comprehension but also assists teachers in delivering materials more efficiently. Given its effectiveness, further research is recommended to explore its broader application across different subjects and educational levels to maximize its impact on learning outcomes.